PENGGUNAAN TEPUNG DUCKWEED (Lemnaceae spp) DALAM RANSUM TERHADAP BERAT RELATIF HATI DAN PANKREAS AYAM PEDAGING - Ummiani Hatta; Rusdi Rusdi; Rosmiaty Arief (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research aimed to study the effect of adding duckweed smash to broiler chicken feed on relative weight of its liver and pancreas. The number of chicken used was 100 broilers. The study employed a Completely Randomized design with five replicates in which five broilers were used for each replicate.  The treatments included basal feed (R0), 97% basal feed with 3% duckweed smash (R1), 94% basal feed with 6% duckweed smash (R2), 91% basal feed with 9% duckweed smash (R3), and 88% basal feed with 12% smash duckweed (R5). The addition of the duckweed smash on broiler feed significantly increased both the relative weight of the broiler liver and pancreas.